Basidiobolomycosis Successfully Treated With Fluconazole - Bandyopadhyay Debabrata; Chowdhury Satyendra Nath (Wolters Kluwer Medknow Publications, 1996)
A case of basidiobolmycosis in a young housewife whose condition responded to a course of fluconazole is reported.